Planar Photonic Crystal Biosensor for Quantitative Label‐Free Cell Attachment Microscopy. Issue 11 (22nd August 2015) - Chen, Weili; Long, Kenneth D.; Kurniawan, Jonas; Hung, Margaret; Yu, Hojeong; Harley, Brendan A.; Cunningham, Brian T.
Abstract : In this study, a planar‐surface photonic crystal (PC) biosensor for quantitative, kinetic, label‐free imaging of cell–surface interactions is demonstrated. The planar biosensor surface eliminates external stimuli to the cells caused by substrate topography to more accurately reflect smooth surface environment encountered by many cell types in vitro. Here, a fabrication approach that combines nanoreplica molding and a horizontal dipping process is used to planarize the surface of the PC biosensor. The planar PC biosensor maintains a high detection sensitivity that enables the monitoring of live cell–substrate interactions with spatial resolution sufficient for observing intracellular attachment strength gradients and the extensions of filopodia from the cell body. The evolution of cell morphology during the attachment and spreading process of 3T3 fibroblast cells is compared between planar and grating‐structured PC biosensors. The planar surface effectively eliminates the directionally biased cellular attachment behaviors that are observed on the grating‐structured surface. This work represents an important step forward in the development of label‐free techniques for observing cellular processes without unintended external environmental modulation. Abstract : A planar‐surface photonic crystal biosensor for quantitative, kinetic, label‐free imaging of cell–surface interactions is demonstrated. The planar biosensor surface eliminates external stimuli to the cells caused by substrate topography. This work represents an important step forward in the development of label‐free techniques for observing cellular processes without unintended external environmental modulation.